The Effect of Empirically-determined Beta, Firm Size and Seasonal Patterns on Overreaction Effect in Chinese Stock Market: Evidence from A shares and B shares - YANG, Qian (2017)
The overreaction effect has been a heated topic since it was brought up by De Bondt and Thaler (1985) and was explored internationally since then. This dissertation mainly checks the existence of overreaction effect and the impact from differential beta, differential size and seasonality on the overreaction effect result. The overreaction effect still exists after adjusting for beta and size in Chinese stock market. Although not so significant, based on the five-year ranking period, the contribution of February seems to be larger than the annual return difference after annualization. The beta, size and piror return model have more explanatory power for B shares than for A shares and the middle-sized firm of B shares market seems to contribute more to its overreaction result.